2018
DOI: 10.1016/j.cgh.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prescription of Opiates and Mortality in Patients With Inflammatory Bowel Diseases in England

Abstract: In an analysis of primary care patients with IBD in England, we found prescriptions for opiate drugs to have increased significantly from 1990 through 2013. Heavy use of strong opiates among patients with IBD associates with increased all-cause premature mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
54
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 33 publications
1
54
0
2
Order By: Relevance
“…11 Another study failed to show a statistically significant mortality difference between prescription of tramadol alone or in combination with codeine compared with infrequent or no prescription of tramadol alone or combined with codeine among 8866 patients with Crohn disease and ulcerative colitis. 12 In a large propensity score-matched cohort study that examined the safety of 5 commonly prescribed opioids among 31 375 Medicare beneficiaries in the United States, initial prescription of tramadol was not associated with a statistically significant Abbreviations: COX-2, cyclooxygenase 2; HR, hazard ratio; NSAIDs, nonsteroidal anti-inflammatory drugs; OA, osteoarthritis; PS, propensity score; RD, rate difference. a Asymmetric trimming was used to exclude participants whose propensity score was below the 2.5th percentile of the propensity score of the tramadol cohort and above the 97.5th percentile of the propensity-score of the comparator cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Another study failed to show a statistically significant mortality difference between prescription of tramadol alone or in combination with codeine compared with infrequent or no prescription of tramadol alone or combined with codeine among 8866 patients with Crohn disease and ulcerative colitis. 12 In a large propensity score-matched cohort study that examined the safety of 5 commonly prescribed opioids among 31 375 Medicare beneficiaries in the United States, initial prescription of tramadol was not associated with a statistically significant Abbreviations: COX-2, cyclooxygenase 2; HR, hazard ratio; NSAIDs, nonsteroidal anti-inflammatory drugs; OA, osteoarthritis; PS, propensity score; RD, rate difference. a Asymmetric trimming was used to exclude participants whose propensity score was below the 2.5th percentile of the propensity score of the tramadol cohort and above the 97.5th percentile of the propensity-score of the comparator cohort.…”
Section: Discussionmentioning
confidence: 99%
“…7 Few studies have examined the relationship between tramadol prescription and all-cause mortality, and current evidence regarding the association of tramadol with mortality rates compared with other analgesic medications is inconclusive. [8][9][10][11][12][13] The present study examined the association of initial prescription of tramadol with all-cause mortality compared with alternative commonly prescribed analgesics in patients with osteoarthritis.…”
mentioning
confidence: 99%
“…As evidenced above, hypoalgesic IBD patients demonstrate significantly better quality of life scores than their symptomatic counterparts with active disease, and exhibit symptom profiles that are similar to their quiescent counterparts. Although there are clearly consequences to the lack of appropriate symptomatology in the setting of IBD, conditions defined more by the presence of symptoms such as abdominal pain rather than an overt inflammatory process, including irritable bowel syndrome (IBS), might benefit from alternative approaches to pain management, particularly when we consider the lack of efficacy and/or toxicity of the available analgesics frequently utilized to manage disorders associated with chronic abdominal pain, including NSAIDs and opiates [26][27][28][29]. Notably, our study demonstrated an independent association between hypoalgesic IBD and mesalamine.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, use of pain medication was viewed negatively, be this due to apprehension over side effects or associated longterm risks with stronger pain medication. Opioid dependence is becoming an increasingly recognised issue in IBD, with prevalence rates rising in England (29) and the USA (30). Ample evidence now demonstrates the clinical characteristics and associated risks of long-term opioid use, including psychiatric diagnosis, hospitalisation and development of narcotic bowel syndrome (31,32).…”
Section: Discussionmentioning
confidence: 99%